Corporate Crime Announcement Effect on Stock Price and Its Determinants in Malaysia - Nurul Izza, Abd Malek; Rossazana, Ab Rahim; Nur Zaimah, Ubaidillah; Michelle Chang, Ting Ting (WSEAS. Unifying Science and Engineering, 2023)
Nowadays, the increasing cases of crimes committed by corporations have posed challenges to enforcement agencies, especially in Malaysia. It may result in serious damage to financial institutions and economic performance, as well as generate social disorganisation and lower the level of confidence between investors and consumers. This study aims to examine the reactions of corporate crime announcements on stock prices and identify relationships among determinants of stock prices such as firm size, price to book value, earnings per share, and dividends per share in the context of firms involving crime. The sample consists of 11 announcements by 9 publicly listed companies charged by the Securities Commission for committing a corporate crime from 2003 to 2020, with a total observation of 162. The market model event study and fixed effect regression analysis are employed to analyze the data obtained from Yahoo Finance and Bursa Malaysia. The finding indicates that the AARs on the announcement date are not significant at the 5% level. However, the CAARs on the announcement date were negative abnormal returns and statistically significant. This reveals that the stock market is not reacting efficiently to the announcement of corporate crime because the stock price was not fully reflected in all publicly available information. Furthermore, the results of the fixed effect model revealed that firm size and dividend per share have a significant effect on stock price, whereas price-to-book value and earnings per share have insignificant relationships with stock price in the context of firms involved in corporate crime. This study intends to provide a better understanding of the causes of corporate crime and prevent corporate crime from becoming widespread in the country, thereby reducing the number of corporations that participate in crime.